Codex Zacynthius: catena, palimpsest, lectionary - Houghton, H. A. G.; Parker, David C. (Texts and studies, 2021)
Frontmatter -- TABLE OF CONTENTS -- FOREWORD BY THE UNIVERSITY LIBRARIAN -- ACKNOWLEDGEMENTS -- PREFACE AND PROJECT OUTPUTS -- ABBREVIATIONS -- CHAPTER 1. HISTORY OF RESEARCH ON CODEX ZACYNTHIUS -- CHAPTER 2. THE CODEX ZACYNTHIUS PROJECT -- CHAPTER 3. THE UNDERTEXT WRITING -- CHAPTER 4. THE GOSPEL OF LUKE IN THE PALIMPSEST -- CHAPTER 5. THE LAYOUT AND STRUCTURE OF THE CATENA -- CHAPTER 6. THE SOURCES OF CODEX ZACYNTHIUS AND THEIR TREATMENT (PANAGIOTIS MANAFIS) -- CHAPTER 7. A QUESTION OF ATTRIBUTION: THE THEOLOGICAL SIGNIFICANCE OF THE CATENA IN CODEX ZACYNTHIUS -- CHAPTER 8. CATENAE ON LUKE AND THE CATENA OF CODEX ZACYNTHIUS (PANAGIOTIS MANAFIS) -- CHAPTER 9. AN INTRODUCTION TO LECTIONARY 299 -- APPENDIX 1. CONCORDANCE OF OVERTEXT AND UNDERTEXT PAGES -- APPENDIX 2. CODEX ZACYNTHIUS: THE CATENA AND THE TEXT OF LUKE -- BIBLIOGRAPHY -- INDEX OF MANUSCRIPTS -- INDEX OF ANCIENT WRITINGS -- INDEX OF SUBJECTS